Pendampingan Scale Up Aspek Pemasaran Usaha Younk Cookies dengan Pendekatan Model Project-Based Learning - Pratama, Aryan; Anggriani, Rini; Faerrosa, Lady; Dewi, Puspita; Meilyana; Arsana, I Made Mangku; Akib, Nasifa Tridasari (Insan Kreasi Media, 2023)
Digital transformation has played an important role in the sustainability of Micro, Small and Medium Enterprises (MSMEs). The use of digital platforms as a marketing strategy continues to show rapid development and has been able to expand market reach. However, not all MSME actors are able to adapt in their implementation and application independently due to low understanding of digital literacy. This community service is intended to encourage and determine solutions to problems in the marketing aspect in the digital era through a Project-Based Learning approach. Through this activity, business actors are able to identify and recognize the problems they are facing and find solutions to these problems. The use of Instagram social media in product marketing can be used as an effective promotional medium that has an impact on expanding market reach, increasing brand awareness, increasing production and sales. In the future, it is also expected to increase the capacity of financial management and digital payments.